Comparison of Outcome of Borderline and Normal Amniotic Fluid Index in Term Pregnancy - Ansari, S. N.; Baral, J.; Gurung, G.; Jha, A. (Kathmandu University Medical Journal, 2021)
Background Determination of Amniotic Fluid Index (AFI) is an important component of antepartum assessment of all normal pregnancies. Objective To compare the obstetric interventions and neonatal outcomes in term pregnancies with borderline Amniotic Fluid Index versus normal Amniotic Fluid Index. Method This hospital based prospective study was conducted at Tribhuwan University Teaching Hospital over 1 year between 2017 and 2018 in 128 women having uncomplicated term pregnancy admitted in labor ward. Of the 128 women, 64 women had borderline Amniotic Fluid Index (5.1-8 cm) and 64 normal AFI (8.1 - 24 cm). Parameters studied were induction of labor, cesarean section, instrumental delivery, intrapartum abnormal fetal heart rate, meconium staining of liquor, APGAR score at 5 and 7 minutes, birth weight, neonatal intensive care unit (NICU) admission and neonatal death. Data was analyzed using software OpenEpi. Result Statistically significant difference in result was obtained in the two groups in terms of rate of induction of labor (73.4% vs 35.9%, p = 0.0001, OR = 4.9), rate of cesarean section (42.1% vs 28 .1%, p = 0.04, OR = 1.8), tachypnea (50% vs 11.1%, p = 0.01) and low birth weight (9.1% vs 4.5%, p = 0.04). No statistical significance was found in meconium staining of liquor (33% vs 38.3%, p = 0.3) and APGAR score of <7 at 5 minutes (3.1% vs 1.5%, p = 0.06). There were no neonatal intensive care unit admissions and neonatal mortality in any of the babies. Conclusion Detection of amniotic fluid volume at term is important for timely maternal interventions to improve the overall fetal outcome.